2013
DOI: 10.4244/eijv9i4a79
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human evaluation of the novel BioMime sirolimus-eluting coronary stent with bioabsorbable polymer for the treatment of single de novo lesions located in native coronary vessels - results from the meriT-1 trial

Abstract: The novel BioMime SES demonstrated excellent performance in single coronary lesions including high procedural success and efficacy, as demonstrated by the relatively low late lumen loss (a surrogate of neointimal hyperplasia) at eight-month angiographic FU. Overall, there were no safety concerns in this preliminary evaluation including absence of MACE or ST up to 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…The sirolimus formulated with the biodegradable polymer releases into the treated vessel during 30–40 days after stent implantation 11 . The first-in-man study of BioMime SES has demonstrated excellent performance in CAD patients including high procedural success (100%) and clinical performance 12 …”
Section: Introductionmentioning
confidence: 99%
“…The sirolimus formulated with the biodegradable polymer releases into the treated vessel during 30–40 days after stent implantation 11 . The first-in-man study of BioMime SES has demonstrated excellent performance in CAD patients including high procedural success (100%) and clinical performance 12 …”
Section: Introductionmentioning
confidence: 99%
“…The BM shares with the well-studied BioMime™ DES technological characteristic (sirolimus elution, biodegradable polymeric carrier and ultrathin stent struts) associated with low late lumen loss and reduced hazard of thrombus formation in both studies [11][12][13][14][15] and meta-analyses [16,17]. The primary safety and efficacy trials meriT-1 [18] and meriT-2 [19] and, more recently, the observational post-marketing multisite registry meriT-3 [14] reported low rates of major adverse cardiovascular events (MACEs) and late stent thrombosis. Finally, the randomized meriT-5 trial [20] demonstrated that BM was non-inferior to the XIENCE DES at 9-month follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…This stent was evaluated in the first-human-use meriT-1 study (NCT01507519) which included 30 patients [106]. The study demonstrated median 8-month in-stent late lumen loss was 0.15 mm [0.09, 0.33].…”
Section: Clinical Trials Of Bioabsorbable Polymer-coated Desmentioning
confidence: 99%
“…The study demonstrated median 8-month in-stent late lumen loss was 0.15 mm [0.09, 0.33]. At 12 months, no cardiac deaths, MI, TLR, or ST [106]. …”
Section: Clinical Trials Of Bioabsorbable Polymer-coated Desmentioning
confidence: 99%